Analysis of Participatory Development Implementation in Bantimurung Village, SimbangDistrict, Maros Regency - arni (PT. Anagata Sembagi Education, 2024)
This research aims to explore the implementation of participatory development in Bantimurung Village, Belopa Utara District, Maros Regency, and identify the factors influencing its implementation. The research adopts a descriptive analysis approach, aiming to offer a systematic, factual, and accurate portrayal of existing data regarding participatory development in Bantimurung Village. Data were gathered through observation techniques, in-depth interviews, and literature studies. The findings reveal that participatory development in Bantimurung Village has been effectively executed across various stages, including planning, execution, and evaluation/monitoring. However, to enhance active participation, improvements are needed in each stage. Additionally, several factors influencing the implementation of participatory development in Bantimurung Village were identified, categorized as supporting and inhibiting factors. Supporting factors include the leadership of the Village Head, community participation, facilitator activity, budget availability, and clear regulations. On the other hand, inhibiting factors encompass land acquisition challenges, the role of non-governmental organizations, and human resources issues.